2022
DOI: 10.3389/fmars.2021.830590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Concentration on the Alkalophilic Microalga Nitzschia sp. NW129-a Promising Feedstock for the Integrated Production of Lipids and Fucoxanthin in Biorefinery

Abstract: Microalgae are considered promising resources for producing a variety of high-value-added products, especially for lipids and pigments. Alkalophilic microalgae have more advantages than other microalgae when cultured outdoors on a large scale. The present study investigated the comprehensive effects of different nitrogen concentrations on fucoxanthin (Fx), lipids accumulation and the fatty acid profile of the alkaliphilic microalgae Nitzschia sp. NW129 to evaluate the potential for simultaneous production of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Previously, the growth of Conticribra weissflogii and P. tricornutum was suppressed in the media without nitrogen supply [28,29], while Nitzchia sp. biomass was greatly reduced under limited nitrogen conditions [24]. On the contrary, the highest dry biomass of C. weissfloggii (0.75 g/L) and Nitzchia sp.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Previously, the growth of Conticribra weissflogii and P. tricornutum was suppressed in the media without nitrogen supply [28,29], while Nitzchia sp. biomass was greatly reduced under limited nitrogen conditions [24]. On the contrary, the highest dry biomass of C. weissfloggii (0.75 g/L) and Nitzchia sp.…”
Section: Discussionmentioning
confidence: 88%
“…By examining the effect of various nitrogen concentrations on FX production, Afonso et al [27] indicated that an increase in initial nitrogen concentration considered resulted in the enhanced FX content in P. tricornutum. Relevant findings have also indicated this universal effect of nitrogen availability on FX accumulation in other microalgae, such as Nitzchia sp., O. aurita, and C. weissflogii species [22,24,26]. Specifically, the highest FX content (~1.5 mg/g) was obtained from C. weissflogii cultured in the 2 N group, which was 4.5 and 1.4 times higher than those in the 0 N and 1 N cultures, respectively [28].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The unselective enrichment of the culture medium (f > f/2, Figure 8 ) additionally supported faster growth rate, stronger biomass accumulation and higher Fx production in F. cylindrus , independent of the temperature. Medium enrichment is a common way of increasing Fx production [ 94 ] (by up to 3-fold [ 97 ]), either through nitrogen [ 32 , 33 , 34 , 76 , 93 , 98 ], iron [ 97 ], silicates and/or CO 2 enrichment of the cultures [ 95 , 99 ]. Additionally, nutrient shortage, and to a larger extent environmental stresses (e.g., high salinity, UV exposure, etc.…”
Section: Discussionmentioning
confidence: 99%